Micrometrical, Histological and Histochemical Studies on the Prostate Gland of Bakerwali Goat (Kaghani). - Nissar, Shazia; Suri, Shalini (Indian Journal of Veterinary Anatomy, 2018)
The prostate glands of adult (29) and senile (6) Bakerwali goat were utilized for recording micrometrical, histological and histochemical parameters. In Bakerwali goat the prostate gland comprised of only disseminate part of prostate gland (pars disseminata prostate) and corpus prostatae was absent in goat. The pars disseminate was compound tubulo-alveolar gland surrounded by connective tissue capsule and encircled by urethralis muscle. The serous secretory end-pieces (alveoli, tubules and ducts) were lined with cuboidal epithelium, while the collecting ducts were lined with stratified cuboidal epithelium. The mucous end-pieces were lined with tall columnar epithelium with oval nuclei. The secretory unit of pars disseminates prostate consisted of solid and luminated end pieces distributed in the wall of pelvic urethra. The nuclei of solid end pieces were rounded in shape. These solid end pieces also showed secretory activity as diastase resistant PAS positive granules in adult group of Bakerwali goat. Mild cholesterol reaction was also observed in solid end pieces. Closer to urethral lumen, just below the lining epithelium, aggregation of lymphocytes was also observed. Cholesterol was observed at apical border and basal border of lining epithelium of alveoli, tubules and ducts.